2000
DOI: 10.1111/j.1553-2712.2000.tb00480.x
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Analysis of Process Errors in Trauma Resuscitations

Abstract: Abstract. Objective: A computer-based system to apply trauma resuscitation protocols to patients with penetrating thoracoabdominal trauma was previously validated for 97 consecutive patients at a Level 1 trauma center by a panel of the trauma attendings and further refined by a panel of national trauma experts. The purpose of this article is to describe how this system is now used to objectively critique the actual care given to those patients for process errors in reasoning, independent of outcome. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 6 publications
0
54
0
1
Order By: Relevance
“…1,2 Errors occur because of time pressure, inexperience, reliance on memory, multitasking, and failures in trauma team coordination, especially during the initial minutes of patient reception and resuscitation. [3][4][5][6] Human variables that confound a standardized environment and lead to avoidable errors have been addressed by the airline and other industries. For example, computerized prompts are built into flightcontrol systems, providing immediate feedback and error avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Errors occur because of time pressure, inexperience, reliance on memory, multitasking, and failures in trauma team coordination, especially during the initial minutes of patient reception and resuscitation. [3][4][5][6] Human variables that confound a standardized environment and lead to avoidable errors have been addressed by the airline and other industries. For example, computerized prompts are built into flightcontrol systems, providing immediate feedback and error avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…12 One study of trauma patients found that there were reasoning errors in 100% of trauma resuscitations. 13 The use of heuristics is a necessary evil in caring for ED patients. The use of heuristics is inevitable to allow clinicians to maintain efficiency and not chase the metaphorical zebras (a colloquial term designating those possible diagnoses that are least likely and most difficult to confirm on the basis of given clinical data, as in the saying, ''when you hear hoofbeats, think horses, not zebras'').…”
Section: Discussionmentioning
confidence: 99%
“…Team leaders often do not (or will not) follow basic protocols [47][48][49]. Medical errors tend to occur more frequently in stochastic environments or when team dynamics and communication are flawed [18,[50][51][52][53].…”
Section: Team Focus and Errorsmentioning
confidence: 99%